2022
DOI: 10.5070/g601139
|View full text |Cite
|
Sign up to set email alerts
|

Is reanalysis selective when regressions are consciously controlled?

Abstract: The selective reanalysis hypothesis of Frazier and Rayner (1982) states that when faced with the need to reanalyze a syntactic ambiguity, readers direct their eyes towards the region in the sentence inducing the ambiguity (e.g., Since Jay always jogs a mile seems like a short distance to him). Given the mixed evidence for this proposal in the literature, we investigated the possibility that selective reanalysis is tied to conscious awareness of the garden-path effect. To this end, we adapted the well-known sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 72 publications
1
33
1
Order By: Relevance
“…4 After having been garden-pathed, the parser can either apply triage or carry out covert reanalysis, which is very costly (579-690 ms). A third alternative, namely making a regression, is also very costly (494-617 ms), which however may be due to the more deliberate nature of regressive rereading in the BSPR paradigm compared to natural reading (Paape & Vasishth, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 After having been garden-pathed, the parser can either apply triage or carry out covert reanalysis, which is very costly (579-690 ms). A third alternative, namely making a regression, is also very costly (494-617 ms), which however may be due to the more deliberate nature of regressive rereading in the BSPR paradigm compared to natural reading (Paape & Vasishth, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that surprisal alone cannot account for the magnitude of garden-path effects suggests that Deep Learning models may need to be augmented with additional mechanisms if one wants to use them as realistic models of human sentence processing. One important factor in this regard may be the involvement of conscious awareness in garden-path processing, which has often been invoked in the classical psycholinguistic literature (e.g., Frazier & Rayner, 1982;Marcus, 1980;Pritchett, 1992): In human readers, strong garden paths like the one caused by the NP/Z ambiguity often lead to a conscious experience of processing difficulty, as well as temporary or permanent processing breakdown, and may require deliberate rereading and reanalysis (e.g., Gibson, 1991;Paape & Vasishth, 2022). Language models lack consciousness, which may be part of the reason why they do not fully capture the human data in this specific domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, no psycholinguistic theory exists that would be able to predict the occurrence of overt versus covert reanalysis in a particular trial. It has been suggested that overt reanalysis is used to resolve difficulties with diagnosing the source of the first‐pass parsing error (Frazier & Rayner, 1982) and that it may involve conscious, deliberate reprocessing (Paape & Vasishth, 2022). A relevant intuition is that rereading should be more likely when memory demands are high (Meseguer, Carreiras, & Clifton, 2002), but there may be large individual differences between readers (Rayner & Sereno, 1994) and presumably between experimental items as well.…”
Section: Introductionmentioning
confidence: 99%